Situation Report: Poland, 18 January 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Inquiry into Holland's Death A British Woman of Polish Origin Accused of Spying Sitdown Strikes Technical Hinterland of Agricultural Circles Neglected Agronomists - Progress Report An Appeal for More US-Polish Trade Amendments to New Law on Supreme Court Culture Polish Journalist on the Cult of Stalin in Georgia